Risk perception on adoption intention of digital economy: an integration of perceived risk theory with TAM model. (17th June 2021) - Priya, A.R. Shanmuga; Poonguzhali, P.; Krishnaraj, R.; Suresh, V.
Since the global economy is tuning their way towards digital economy, the cashless transactions has bubbled a giant threat with the people in adopting full fledged online transactions and a biased perception exist in the transmission of cashless economy. This article explores a combined model of TAM, perceived risk theory and perceived benefit, the theories hugely used in the research works of technology adoption. The model was analysed using PLS-SEM and the respondents were general public with different demographic category who provided the data. The results of the study show that perceived risk, perceived benefit, perceived ease of use and perceived use influence the intention of individuals to commit digital economy. The attitude of the individuals towards digital economy is also found to be influenced by perceived risk, perceived benefit, perceived ease of use and perceived use.